PREVALENCE OF CLOSTRIDIUM PERFRINGENS AND CLOSTRIDIUM PERFRINGENS-LIKE ORGANISMS IN FAECAL SAMPLES OF DOMESTIC ANIMALS - Awad Al-Kareem Hussain, Manal; Mohamed El Sanousi, Sulieman (Journal of Veterinary Medicine and Animal Production, 2022)
The aim of this study was to determine the prevalence of Clostridium perfringens and C. perfringens like organisms in domestic ruminants, equines and chicken and to clarify the confusion between these organisms. In this study, two hundred and ten faecal samples were collected from seven animal species (cattle, sheep, goats, camels, horses, donkeys and chicken. Thirty samples were taken from each species. The faecal samples were cultured into cooked meat medium and then subcultured on blood agar under anaerobic condition. Pure colonies were identified to the species level using biochemical tests, lecithinase production as well as synergistic hemolysis. Out of the 210 faecal samples, 130 isolates of C. perfringens and C. perfringens-like organisms were isolated. 50 isolates were Clostridium perfringens which constituted 38.5% of them i.e., with a prevalence rate of 23.8% in the animals tested. Eighty isolates (61.5%) were C. perfringens-like organisms which included C. sardiniensis, C. absonum, C. beijerinckii, C. celatum and C. barati, with prevalence rates of 27.6%, 4.8%, 3.3%, 1.9% and 0.5%, respectively. Chicken gave the greatest number of C. perfringens followed by donkeys and then camels, while the greatest number of C. perfringens- like organisms was detected in camels and then donkeys. The results revealed that C. perfringens and C. perfringens-like organisms were detected in all animal species examined with varying percentages and not be overlooked during the process of isolation of C. perfringens.